Pooling resources to drive quality; the evolution of the National Audit Tools Group (NATG). Issue 2 (1st September 2011) - Rodgers, Carol; Flanagan, Pauline; Thompson, Andrew
Abstract : Introduction: Recognising the importance of audit in improving quality and the limited resources available in many hospices, Help the Hospices formed the NATG in 2004. Aim: To pool expertise from across the hospice movement to develop a core range of hospice-specific audit tools that are available to all. Method: Initial membership comprised a small multi-professional team of hospice personnel with a specific interest in audit and quality. To establish an effective methodology, they started by developing audit tools relating to core areas of treatment and care. As more professionals volunteered to participate, the group expanded and subgroups were formed to develop new ranges of tools. The active involvement of experts from particular fields was sought to inform and strengthen this process. To encourage their widespread use, tools are designed to be user-friendly, and are trialled rigorously before release. Feedback from trials and subsequent usage has led to progressive improvements in design. Results: Representatives from 29 hospices are members of the group/subgroups, and over 50 hospices have trialled new tools. 22 audit tools have been released to date and downloads from Help the Hospices website have averaged over 400 per month. Evolution of the group is ongoing with seven subgroups currently developing another 13 audit tools, including new families of tools for community services and children's hospices. Discussion: The commitment of a broad range of personnel from different backgrounds, supported by their local hospices, has been key to the successful evolution of the NATG. Membership of subgroups or attendance at workshops provides excellent training opportunities. Possible future projects include e-learning, benchmarking and validation of locally-generated tools. Conclusion: The NATG has developed a highly effective model for pooling expertise to drive quality improvement by facilitating audit.